Pengawasan Camat Dalam Penyelenggaraan Pemerintahan Di Kantor Kecamatan Soyo Jaya Kabupaten Morowali Utara - M Syukur; Mohammad Rizal Mamala; Nuraisyah Nuraisyah (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2021)
This research is to find out how the Camat Supervision in Government Administration at the Soyo Jaya District Office, North Morowali Regency. The types of data used are primary data and secondary data. Data collection techniques, carried out through observation, interviews, and documentation. Informant withdrawal technique using purposive. The number of informants in this study amounted to 5 people. The theory used is the theory of Siagian, which consists of 2 (two) aspects, namely: direct supervision and indirect supervision. Based on the results of the research conducted, that the Soyo Jaya Camat in organizing activities carried out by his employees (subordinates), has not been able to work effectively and efficiently and the supervision process carried out by the Soyo Jaya Camat is inconsistent and not carried out properly, it has an impact on performance. the organization as a whole is primarily concerned with the discipline of the state civil apparatus (ASN). The data found by researchers in the field lead to indications that the implementation of supervision is not going well, it can be seen from the emergence of several problem phenomena, namely the Camat is less regular in checking employee attendance through attendance, so that it has an impact on the organization of activities and has an impact on employee flexibility. in committing fraud against filling absenteeism by entrusting attendance attendance. In addition, the lack of directives and explanations by the Camat to employees regarding the rules and guidelines in every work implementation given to employees, so that compliance with the implementation of work is often ignored by employees which has an impact on work results that are less than optimal. Thus, from the two aspects of supervision above, there are still several things that need to be addressed, so that the supervision provided can be maximized